Pengaruh Pengendalian Internal terhadap Akuntansi Ekuitas pada Bank: Kajian pada Bank Umum dan Bank Perkreditan Rakyat - Billy Marbiyanov; Muhammad Naufal Fitrah; Ricky Sandy Permana; Roy Mangitua Manurung; Yoma Arda Wiratama (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the influence of internal control on equity accounting in banks, specifically focusing on both Commercial Banks and Rural Banks (Bank Perkreditan Rakyat/BPR). The discussion emphasizes several key aspects of banking equity, including the definition of bank capital, its classification, and the calculation of capital adequacy ratios. The research employs a qualitative descriptive method through a literature review of relevant academic sources and financial regulations issued by financial authorities such as OJK (Financial Services Authority of Indonesia). An effective internal control system plays a crucial role in ensuring the reliability and accuracy of financial reporting, particularly in the recording and presentation of bank equity. It also helps maintain compliance with regulations and supports the resilience of the banking sector. The study finds that internal control significantly contributes to transparent and accountable equity management, enabling banks to present their financial positions more accurately and protect stakeholders’ interests.Furthermore, internal control mechanisms such as authorization procedures, reconciliation processes, segregation of duties, and regular internal audits are essential in preventing errors and fraud in equity-related transactions. Properly implemented, these controls not only enhance the credibility of financial statements but also strengthen a bank’s capital structure and overall financial stability. This research highlights the importance of internal control as a foundational pillar for effective equity accounting in the banking industry.